Digital Literacy Assisted by E-Litera Media Nonfiction Text Materials to Increase Interest in Learning - Kardiana Metha Rozhana; Kardiana Zendha Avalentina; Adi Tri Atmaja (Proceeding of the International Conference on Global Education and Learning, 2025)
The objective of this research is to improve student learning interest in nonfiction texts through the implementation of E-Litera, a digital-based interactive literacy media. This study utilized a classroom action research design conducted in two cycles involving 24 fourth-grade students at SDN Sidomulyo. Data were obtained from questionnaires, observations, interviews, and documentation. The results showed a significant improvement in student learning outcomes throughout the research process. In the pre-action phase, only 8 students (33.3%) achieved the minimum mastery criteria, while 16 students (66.7%) did not meet the criteria. This figure increased to 12 students (50%) in the first cycle, and significantly rose to 20 students (83.3%) in the second cycle. The enhanced performance in the final cycle reflects the effectiveness of E-Litera in providing visually engaging and structured content, which helped deepen students' understanding of nonfiction materials. These findings support the use of E-Litera as a meaningful and engaging digital media to foster reading interest and improve comprehension skills in elementary education. By using E-Litera, the teaching and learning process can be more effective and enjoyable, ultimately improving the quality of student learning.